Hannah van Bart - Bart, Hannah van 1963-; Biswas, Allie; Hartog Jager, Hans den 1968- (Jap Sam Books, 2023)
The monograph Hannah van Bart contains over more than 100 art works (paintings and drawings) and gives an intriguing look at the work of Dutch artist Hannah van Bart (1963). The publication is published in collaboration with the Centraal Museum Utrecht on the occasion of the solo exhibition of Hannah van Bart at Oud Amelisweerd country house. Hannah van Bart is represented by Marianne Boesky Gallery New York & Aspen, and Vielmetter Los Angeles. With a foreword by Artistic director of Centraal Museum Bart Rutten, an interview by London-based art critic Allie Biswas with Hannah van Bart, and an essay on the work of the artist by writer and art critic Hans den Hartog Jager. Anyone viewing Hannah van Bart's paintings for a length of time will be prompted to return to them again and again. Her works are invigorating and have enormous psychological depth. Beauty and discomfort go hand in hand. Not the pursuit of capturing a moment, like you see in photography or a studio sketch, but a long process of turning things over in one's mind, painting and erasing, adding and taking away. This process provides an interestingly hard edge to her paintings. Exhibition: Landhuis Oud Amelisweerd, Bunnink, The Netherlands (01.04. - 20.08.2023)
Colophon: This book was published on the occasion of the solo exhibition by Hannah van Bart at Oud Amelisweerd country house, organised by the Centraal Museum (April 1st - August 20th 2023)
Keywords: Bart, Hannah van -- 1963-; Zeichnung; Malerei; Ausstellungskatalog -- Landhuis Oud Amelisweerd -- 01.04.2023-20.08.2023 -- Bunnik; Bildband